Did Monetary Policy Kill the Phillips Curve? Some Simple Arithmetics - Bergholt, Drago; Furlanetto, Francesco; Vaccaro-Grange, Etienne (The Review of Economics and Statistics, 2024)
Abstract An apparent disconnect has taken place between inflation and economic activity in the pre-COVID US economy, causing some to believe that the Phillips curve has flattened. We argue that this view may be premature. Using New Keynesian theory and estimated SVAR models, we decompose fluctuations in US macro data into the components driven by demand and supply disturbances, and confront the inflation disconnect with some simple arithmetics. This exercise confirms a relatively stable Phillips curve slope while the demand curve has flattened substantially. Our results are consistent with a shift towards firmer monetary policy commitment to inflation stability.